Hsp104: a specialized chaperone for protein disaggregation - Glover, John R. (Henry Stewart Talks, 2007)
Heat shock, Molecular chaperones and thermotolerance, Protein aggregation and refolding, Prions in mammals and yeast, Molecular chaperones and protein aggregation associated with human disease
Archived at 2021/02/25